Securing IEC60870-5-101 Communication Protocol using SCADA Cryptographic and Device Authentication Gateway - Qassim Q.S.; Jamil N.; Mahdi M.N.; Ahmad Zawawi M.N.; Jamaludin M.Z.; Jidin R.; Rusli M.E. (Institute of Physics, 2023)
Cryptography; Gateways (computer networks); Communications protocols; Cryptographic algorithms; Cryptographic devices; CryptoGraphics; Device authentications; FPGA technology; Practical solutions; Stuxnet; System security; Authentication